Strategic default in financial networks - Nizar Allouch; Maya Jalloul (Queen Mary University of London, School of Economics and Finance, 2018)
This paper investigates a model of strategic interactions in financial networks, where the decision by one agent on whether or not to default impacts the incentives of other agents to escape default. Agents' payoffs are determined by the clearing mechanism introduced in the seminal contribution of Eisenberg and Noe (2001). We first show the existence of a Nash equilibrium of this default game. Next, we develop an algorithm to find all Nash equilibria that relies on the financial network structure. Finally, we explore some policy implications to achieve efficient coordination.
Keywords: C72; D53; D85; G21; G28; G33; 330; Systemic risk; default; financial networks; coordination games; central clearing; counterparty; financial regulation